MATLAB-based software for Size-Specific Dose Estimation (SSDE) in Computed Tomography Examinations - Khoramian, Daryoush; Sistani, Soroush (Archives of Advances in Biosciences, 2016)
Primary and widely in use Computed Tomography (CT) dose descriptor is a volumetric CT Dose Index (CTDIv) that is usually measured by a pencil ionization chamber with active length of 100mm and polymethyl methacrylate (PMMA) phantom. CTDIv depends on scan parameters such as mAs, kV, collimation, tube rotation time but is independent of patient’s size and shape. For the purpose of a good estimation of dose received by the patients, American Association of Physicists in Medicine (AAPM) published the conversion factors for both 16 and 32cm (head and body phantoms respectively); through this, users can extract conversion factors according to lateral (LAT) and/or anterior-posterior (AP) sizes and calculate real CTDIv. Since this procedure is time consuming, we designed MATLAB-based software to reduce such calculations. To design the software, GUI toolbar of MATLAB software was used. To test the software, scan parameters of two patients for head and pelvis scan were read from PACS and lateral (LAT) and anterior-posterior (AP) sizes were measured. Finally, SSDEs were calculated for two patients by the software. The software can be measured based on AP and/or LAT measures and/or in special cases (under the age of 18) through patients’ age.